A randomised clinical evaluation of a fluoride mouthrinse and dentifrice in an in situ caries model. (March 2018) - Parkinson, Charles R.; Hara, Anderson T.; Nehme, Marc; Lippert, Frank; Zero, Domenick T.
Abstract: Objectives: Fluoride mouthrinses provide advantages for fluoride delivery by maintaining elevated intra-oral fluoride concentrations following fluoride dentifrice use. This in situ caries study investigated potential anti-caries efficacy of a 220 ppm fluoride mouthrinse. Methods: This was an analyst-blinded, four-treatment, randomised, crossover study using partially demineralised, gauze-wrapped, human enamel samples mounted in a mandibular partial denture. Participants brushed twice daily for 14 days with either a 1150 ppm fluoride or a fluoride-free placebo dentifrice and either rinsed once daily with the 220 ppm fluoride mouthrinse or not. Following each treatment period, percent surface microhardness recovery (%SMHR) and enamel fluoride uptake (EFU) were assessed. Results: Fifty three participants completed the study. Compared with the placebo dentifrice/no rinse treatment, the fluoride-containing regimens demonstrated greater enamel remineralisation (%SMHR) and fluoridation (EFU): fluoride dentifrice/fluoride rinse (%SMHR difference: 21.55 [95% CI: 15.78, 27.32]; EFU difference 8.35 [7.21, 9.29]); fluoride dentifrice/no rinse: 19.48 [13.81, 25.15]; 6.47 [5.35, 7.60]; placebo dentifrice/fluoride rinse: 16.76 [11.06, 22.45]; 5.87 [4.72, 7.00] (all P < .0001). There were no significant differences in%SMHR between fluoride regimens. The fluoride dentifrice/fluoride rinse regimen was associated with higher EFU than the fluoride dentifrice/no rinse (1.88 [0.75, 3.01], P = .0013) and placebo dentifrice/fluoride rinse regimens (2.48 [1.34, 3.62], P < .0001). Treatments were generally well-tolerated. Conclusions: The in situ caries model demonstrated that the fluoride mouthrinse is effective in promoting enamel caries lesion remineralisation and fluoridation whether used following a fluoride or non-fluoride dentifrice. Additive (potential) anti-caries benefits of a fluoride rinse after a fluoride dentifrice were confined to enhancements in lesion fluoridation (EFU). Clinical significance: In conjunction with a fluoride dentifrice, fluoride mouthrinses enhance enamel fluoridation, which may be useful in caries prevention.